Association of Risk Factors with Female Pattern Hair Loss (Medicine Today, 2024)
Introduction: Female Pattern Hair Loss (FPHL) is one of the main causes of hair loss in adult women and has a major impact on individual’s quality of life. It evolves from the progressive miniaturization of follicles that lead to a subsequent decrease of the hair density, leading to a non-scarring diffuse alopecia. In spite of the high frequency of the disease and the relevance of its psychological impact, its pathogenesis is not yet fully understood, being influenced by genetic, hormonal, and environmental factors. Objective: To evaluate etiological factors associated with female pattern hair loss. Materials & Methods: This was a hospital-based case control study, conducted in the Department of Dermatology & Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March, 2021 to August, 2022. In this study, total 100 females aged 18 to 45 years were enrolled. Among them, 30 females had history of hair loss >6 months, presented to outpatient department, BSMMU were included as case & 70 healthy females who had no history of hair loss included as control according to inclusion & exclusion criteria. Diagnosis of FPHL was made clinically & Ludwig classifications were used to assess the degree of hair loss. Information on possible risk factors for FPHL was collected using a questionnaire interview. Result: The mean age of the patients with FPHL was 41.0±7.77 years with majority belongs to >40 years of age group & their mean duration of hair loss was 26.3±12.0 months. Among the patients of FPHL, 36.7% had history of inadequate intake of iron containing food, 66.7% had family history of alopecia, 36.7% had history of increased bleeding during their menstruation, 20.0% had multiple (>3) childbirth & 23.3% had hypertension. About 86.7% patients with FPHL had low serum ferritin (